Pengaruh Model Pembelajaran Time Token terhadap Keterampilan Berbicara Siswa Kelas V SD - Haikal Azrasabiy; Lutfi Lutfi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of the Time Token learning model on the speaking skills of fifth-grade students at SD Negeri Parung Bingung 1. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of 58 students, divided into an experimental class (using the Time Token model) and a control class (using direct instruction). Data were collected through speaking skill tests (pre-test and post-test) and analyzed using descriptive and inferential statistical tests. The findings revealed a significant improvement in speaking skills in the experimental class compared to the control class. The average pre-test score of the experimental class increased from 23.67 to 35.03 in the post-test, while the control class improved from 31.07 to 40.11. An independent t-test indicated that the Time Token learning model had a significant effect on students’ speaking skills (p < 0.05). The study concludes that the Time Token model is effective in enhancing students’ speaking skills by providing equal opportunities for each student to speak, reducing anxiety, and promoting active participation in learning. Therefore, this model can serve as an alternative for teachers in developing more interactive and effective teaching methods.